2006
DOI: 10.1074/jbc.m604994200
|View full text |Cite
|
Sign up to set email alerts
|

Native TRPC7 Channel Activation by an Inositol Trisphosphate Receptor-dependent Mechanism

Abstract: In DT40 B lymphocytes, Canonical Transient Receptor Potential 7 (TRPC7) functions as a diacylglycerol-activated non-selective cation channel. However, previous work indicated that the non-store-operated Ca 2؉ entry in this cell type depends upon inositol trisphosphate receptors (IP 3 R). With the cell-attached configuration oleyl-acetyl-glycerol (OAG) induced single channel activity (75 pS) that was not observed in TRPC7 ؊/؊ DT40 cells were indistinguishable from one another and from wildtype cells. Thus, TRPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…When it is expressed at high levels, TRPC7 functions as a storeindependent channel that is inhibited by high concentration of Gd 3+ . By contrast, at low expression level TRPC7 behaves as a SOC, its activity depends on the presence of IP 3 receptors and it is highly sensitive to inhibition by Gd 3+ [25][26][27]. Hence, the function of TRPC7 as SOCs depends on its expression level.…”
Section: Trpc Channels As Socsmentioning
confidence: 97%
“…When it is expressed at high levels, TRPC7 functions as a storeindependent channel that is inhibited by high concentration of Gd 3+ . By contrast, at low expression level TRPC7 behaves as a SOC, its activity depends on the presence of IP 3 receptors and it is highly sensitive to inhibition by Gd 3+ [25][26][27]. Hence, the function of TRPC7 as SOCs depends on its expression level.…”
Section: Trpc Channels As Socsmentioning
confidence: 97%
“…Therefore statistical evaluations of effects were based on paired t-tests. Detailed methods for collection and analysis of TRPC7 single channel data were described previously [14].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore statistical evaluations of effects were based on paired t-tests. Detailed methods for collection and analysis of TRPC7 single channel data were described previously [14].All reagents were purchased from Sigma (St. Louis, MO), except oleyl acetyl glycerol (OAG) (Calbiochem, San Diego, CA) and PIP 2 (Echelon Biosciences Inc., Salt Lake City, UT). …”
mentioning
confidence: 99%
“…However, numerous studies also demonstrated that TRPC channels did not operate as SOCE channels, but rather are gated by second messengers like Ca 2+ or diacylglycerol (DAG; [15][16][17]). Hence, the involvement of TRPC channels in the SOCE mechanism is a controversial issue, and appears to dependent on the cell types investigated, and importantly on the expression level of the TRPC [14,18,19].…”
Section: Introductionmentioning
confidence: 99%